1986
DOI: 10.1677/joe.0.1100417
|View full text |Cite
|
Sign up to set email alerts
|

Reappearance of the thymus in old rats after orchidectomy: inhibition of regeneration by testosterone

Abstract: The thymus is a critically important organ during development, but atrophies progressively during the ageing process after puberty and is often considered to be unimportant in adult life. We have found that the thymus, which is grossly atrophied in 12- to 15-month-old male rats, is markedly restored in size 30 days after orchidectomy. The organ then appears normal histologically, having a well-defined cortex and medulla, is vascularized and filled with thymocytes. The regeneration of the thymus after orchidect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(70 citation statements)
references
References 16 publications
3
65
0
2
Order By: Relevance
“…The thymus is sensitive to sex steroids and, postpuberty, undergoes progressive thymic atrophy, which can be reversed by castration, resulting in significant parallel expansion of both thymocytes and TEC (26,(52)(53)(54). It has been hypothesized that NZB thymic defects occur as a result of premature thymic involution (55,56).…”
Section: Castration Does Not Normalize the Tec Defects In Nzb Micementioning
confidence: 99%
“…The thymus is sensitive to sex steroids and, postpuberty, undergoes progressive thymic atrophy, which can be reversed by castration, resulting in significant parallel expansion of both thymocytes and TEC (26,(52)(53)(54). It has been hypothesized that NZB thymic defects occur as a result of premature thymic involution (55,56).…”
Section: Castration Does Not Normalize the Tec Defects In Nzb Micementioning
confidence: 99%
“…As a consequence, it is deduced that hormones may induce, or at least influence age-associated thymic loss. Lots of evidence suggested that androgen might induce thymus involution by inhibiting thymocyte development and accelerating T cell apoptosis via AR expressed in the thymus (17)(18)(19)(20)(21)(22)(23). Furthermore, several studies suggested that AR in the thymic epithelial part might be responsible for the androgen induced thymic involution (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cells were removed using hypotonic lysis buffer (0.14 M NH 4 Cl buffered with 0.017 M Tris, pH 7.2) for 5 min at room temperature. Remaining cells were incubated with saturating amounts of phycoerythrin-conjugated antimouse CD8 antibodies and fluorescein isothiocyanateconjugated anti-mouse CD4 antibodies (BD PharMingen) and sorted with a FACSAria TM Cell Sorter (Becton Dickenson).…”
Section: Preparation and Sorting Of Thymocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently mentioned that this involution is due to the thymocyte apoptosis induced by exposure to steroid hormones [20]. Gonadectomy, on the other hand, is known to cause thymus hypertrophy, even in aged animals [3,9]. Although these observations suggest that the testis may always exert somewhat inhibitory effect on the thymus, it is well documented that the hypothalamo-pituitary-testicular axis becomes very hypofunctional for a certain period after birth in rats [4].…”
mentioning
confidence: 99%